Tailoring the documentation of plant genetic resources in Europe to the needs of the user: Workshop of the ECPGR Documentation and Information Working Group, 20-22 May 2014, Prague, Czech Republic - Maggioni, L.; Hintum, T.J.L. van; Lipman, E.; Bioversity International; European Cooperative Programme for Plant Genetic Resources (2014)
A Workshop of the Documentation and Information Working Group, “Tailoring the Documentation of Plant Genetic Resources in Europe to the Needs of the User”, was held in Prague, Czech Republic, from 20 to 22 May 2014. This workshop, attended by 49 participants from 29 different countries, gathered a selected group of National Inventory Focal Points, ECPGR Central Crop Database managers and international experts of PGR documentation and informatics. A number of ECPGR National Coordinators and Working Group Chairs also attended. The new coordinator and manager of EURISCO, which is being transferred from Bioversity International, Rome to IPK, Gatersleben, introduced himself and discussed the future short- and medium-term perspectives of the online PGR catalogue. The relationship between EURISCO and the ECPGR Central Crop Databases (CCDBs) was also discussed, based on an extensive survey of the current status of the 48 CCDBs. An agreement was reached, indicating that CCDBs will be encouraged to evolve towards crop portals, providing various types of information of interest for the crop users. The Workshop also discussed documentation of in situ data (crop wild relatives and landraces) and about the future role of genebanks in the genomics era.